Patient assessments of a hypothetical medical error: effects of health outcome, disclosure, and staff responsiveness. Issue 2 (31st March 2006) - Cleopas, A; Villaveces, A; Charvet, A; Bovier, P A; Kolly, V; Perneger, T V
Abstract : Objective: To assess whether patients' perceptions of a hypothetical medical error are influenced by staff responsiveness, disclosure of error, and health consequences of the error. Design: Hypothetical scenario describing a medication error submitted by mail. Three factors were manipulated at random: rapid v slow staff responsiveness to error; disclosure v non-disclosure of the error; and occurrence of serious v minor health consequences. Participants: Patients discharged from hospital. Measures: Assessment of care described in the scenario as bad or very bad, rating of care as unsafe, and intent to not recommend the hospital. Results: Of 1274 participants who evaluated the scenario, 71.4% rated health care as bad or very bad, 60.2% rated healthcare conditions as unsafe, and 25.5% stated that they would not recommend the hospital. Rating health care as bad or very bad was associated with slow reaction to error (odds ratio (OR) 2.8, 95% CI 2.1 to 3.6), non-disclosure of error (OR 2.0, 95% CI 1.5 to 2.6), and serious health consequences (OR 3.4, 95% CI 2.6 to 4.5). Similar associations were observed for rating healthcare conditions as unsafe and the intent to not recommend the hospital. Younger patients were more sensitive to non-disclosure than older patients. Conclusions: Former patients view medical errors less favorably when hospital staff react slowly, when the error is not disclosed to the patient, and when the patient suffers serious health consequences.